Assessing incarcerated women’s physical and mental health status and needs in a Swiss prison: a cross-sectional study - Augsburger, Aurélie; Neri, Céline; Bodenmann, Patrick; Gravier, Bruno; Jaquier Erard, Véronique; Clair, Carole (My University, 2022)
Background. Women make up 5% of the European prison population on average. Almost invisible in prison and health research, and suffering the stigma associated with female offending, incarcerated women are often forgotten, and their specific healthcare needs remain much ignored. Combining face-to-face survey interviews and medical chart data, we aim to assess the health status, healthcare needs, and access to preventive medicine of women incarcerated in Switzerland. Results. Sixty incarcerated adult women participated in a cross-sectional study to assess their life and incarceration histories, physical and mental health problems, medication, and use of medical services. Eligibility criteria were (a) an incarceration of at least four weeks and (b) the ability to provide written informed consent. Exclusion criteria were psychiatric instability and insufficient language competence. Women’s average age was 34.3 years old (SD = 9.8); 45.0% of them were born in Switzerland, 33.3% in Europe and 15.0% on the African continent. Overall, 61.7% of women self-reported physical or mental health problems and 13.3% indicated they were once diagnosed with a sexually transmitted infection. Further, 78.3% of women were active cigarette smokers; more than one in three women reported alcohol use problems and almost one in two women had used at least one illicit drug in the year before incarceration. Depression and perceived stress scores were above clinical cut-off points for more than half of interviewed women. When asked how they rated their health, 68.3% of women felt it had worsened since incarceration. All but four women had accessed prison medical services; however, our study does not indicate whether women’s use of healthcare was indeed adequate to their needs. Conclusions. This study demonstrated incarcerated women’s poor health and health-risk behaviours. Structural changes and gender-responsive health promotion interventions have the potential to improve the health of incarcerated women and help them return to the community in better health.